PENGARUH LATIHAN MENGGIRING BOLA KE BIDANG AMAN TERHADAP KEMAMPUAN MENGGIRING BOLA PADA TIM SEPAKBOLA SMKF IKASARI PEKANBARU - Muhammad Rizky; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The problem in this research is that athletes do not yet have the maximum hat capacity, both during training and in competitions. this can be clearly seen during matches where the ball is easily caught by the opponent, the ball is always out of control when controlled, too difficult to break through the opponent's defense. This type of research is a kind of experimental study to see the effect of physical exercise. The aim of this research was to see the effect of safe driving dribbling on the ability to dribble on the Ikasari Pekanbaru SMKF soccer team. The population in this research is the Ikasari Vocational School football team, which consists of 14 people. The sampling technique is to use total sampling, where the total population is sampled. Data collection techniques were obtained from the pre-test and post-test. The instrument in this research uses dribbling as a tool to measure dribbling skills. The data is then statistically processed to test the normality using the lilifours test at a significance level of 0.05 a. Based on the analysis of the normality of the data X, it gives a LoMax of 0.196 and a Ltable of 0.227 , which means LoMax <Ltable. while the variable Y yields a LoMax of 0.122 and an Ltable of 0.227. This means LoMax <LTable. The analysis was performed by t-test. Based on data analysis and discussion, it can be concluded that there is an effect of the practice of dribbling in a safe field on the ability of dribbling on the Ikasari Pekanbaru Vocational High School football team, as shown by a number of 6,833 and a table of 1,753. Means Tcount > Ttable At the level ɑ = 0.05. Key Words: Safe Dribbling Practice, Safe Dribbling Ability